2021
DOI: 10.1186/s41687-021-00307-z
|View full text |Cite
|
Sign up to set email alerts
|

Post-stroke fatigue: an exploratory study with patients and health professionals to develop a patient-reported outcome measure

Abstract: Background Post-stroke fatigue (PSF) is commonly reported and described as disabling by patients recovering from stroke. However, a major challenge is how to accurately diagnose and assess PSF. Therefore, the aim of this study was to explore PSF as it is experienced by stroke survivors and described by health professionals to guide future development of a PSF-specific PROM. Methods Individual semi-structured interviews were conducted with stroke su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…Some of our findings are consistent with prior studies that similarly found fatigue was complicated by its invisibility, and that stroke survivor and carers' lack of knowledge about fatigue contributed to difficulty coping, adding emotional distress ( 12 ). Individual qualitative studies have also reported stroke survivors feel restricted, frustrated ( 11 ), unprepared, and that fatigue is most noticeable soon after hospital discharge ( 37 , 38 ). The perceived benefits of pacing and physical activity have previously been described ( 10 , 12 , 14 , 37 40 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of our findings are consistent with prior studies that similarly found fatigue was complicated by its invisibility, and that stroke survivor and carers' lack of knowledge about fatigue contributed to difficulty coping, adding emotional distress ( 12 ). Individual qualitative studies have also reported stroke survivors feel restricted, frustrated ( 11 ), unprepared, and that fatigue is most noticeable soon after hospital discharge ( 37 , 38 ). The perceived benefits of pacing and physical activity have previously been described ( 10 , 12 , 14 , 37 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was not always clear in other studies whether people were participating in rehabilition ( 12 ). In two recent studies investigating stroke and/or brain injury fatigue experience only 24–35% of participants were receiving outpatient rehabilitation ( 38 , 41 ). In our study stroke survivors used a range of strategies to optimize energy levels and adapt their rehabilitation schedule to their fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Post stroke fatigue is complex and multidimensional, including emotional, cognitive, physical and social aspects. The accurate diagnosis of post-stroke fatigue and the auxiliary diagnosis suitable for instruments are still not ideal [ 21 ]. In addition, stroke patients may not be immediately aware of their fatigue, which are challenges we need to face.…”
Section: Discussionmentioning
confidence: 99%
“…Fatigue is a very common poststroke complication, with a prevalence of 16-74% [ 1 , 2 ], which is considered one of the symptoms of poststroke depression (PSD) [ 3 ]. However, the fact that patients without depression frequently complain of fatigue necessitates a study of “poststroke fatigue” (PSF) as a specific syndrome [ 4 ].…”
Section: Introductionmentioning
confidence: 99%